Teaching information visualization by exploring their power in engaging users of social media applications - Meirelles, Isabel; Sun, Xiaohua (InfoDesign, 2013)
The paper describes a novel way of introducing methods and approaches of visualizing data to undergraduate students that was conducted during a seven-week module course at the College of Design & Innovation at Tongji University, Shanghai, China. It starts with a brief introduction to the rational and methodology used, followed by an examination of the four pedagogical phases that structured the course, including sample of student work. A discussion provides a critical view of the pros and cons of this pedagogical approach with directions for future curriculum.